Augusto y los templos minorasiáticos. El caso efesio - Lozano, Arminda (Gerión. Revista de Historia Antigua, 2011)
The Romans, after the creation of the province of Asia, rapidly revised the relationship between Efesus and its famous temple, Artemisiion. The focus of this article is on the role Augustu’s played in this city, after his victory over Antonius. We can gain valuable information on this matter from the decree drafted during Claudiu’s reign by the provincial governor, Fabius Persicus. This document contains a series of clauses that give us an insight not only on the relationship between the temple with the city, but also about the problems affecting this most glorious Efesian sanctuary and the efforts to resolve them. Although, for the most part, the mentioned clauses already confirm with the norms previously attributed by Augustus, the text allows for a more detailed consideration of the augustean policy towards them. The present study will analyse in a detailed manner all the questions raised here and provide comments on each of them.